A Review Article on Analytical Techniques for Simultaneous Estimation of Dapagliflozin & Linagliptin - Sumit A. Chavda; Vrushabh S. Patel; Sneha B. Vaghasiya; Vishwa B. Bhut (Asian Journal of Pharmaceutical Research and Development, 2026)
Diabetes mellitus is a chronic metabolic disorder that necessitates combination therapy for optimal glycemic control. This review focuses on analytical techniques developed for the simultaneous estimation of these two agents in bulk and pharmaceutical formulations. Emphasis is placed on UV-spectrophotometric and high-performance liquid chromatography (HPLC) methods owing to their simplicity, accuracy, and cost-effectiveness. The UV-spectrophotometric method employs simultaneous equation techniques at 295 nm for dapagliflozin and 225 nm for linagliptin, exhibiting excellent linearity within 2–10 μg/mL concentration range. Multiple HPLC methods have been reported using C18 columns with varying mobile phases such as phosphate buffer–acetonitrile systems, achieving robust separation and reliable detection at wavelengths between 223–244 nm. All methods were validated according to ICH guidelines, assessing parameters like linearity, precision, accuracy, specificity, and robustness, with correlation coefficients (R²) consistently >0.99, confirming high reliability. Additionally, stability-indicating methods were included to ensure detection of degradation products, supporting quality control applications. Overall, the reviewed analytical methods provide reproducible, precise, and economical approaches for the simultaneous estimation of dapagliflozin and linagliptin.